2012
DOI: 10.3390/v4112853
|View full text |Cite
|
Sign up to set email alerts
|

Sharka: The Past, The Present and The Future

Abstract: Members the Potyviridae family belong to a group of plant viruses that are causing devastating plant diseases with a significant impact on agronomy and economics. Plum pox virus (PPV), as a causative agent of sharka disease, is widely discussed. The understanding of the molecular biology of potyviruses including PPV and the function of individual proteins as products of genome expression are quite necessary for the proposal the new antiviral strategies. This review brings to view the members of Potyviridae fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 387 publications
(355 reference statements)
2
44
0
Order By: Relevance
“…Abbreviations as in Table 2 Brought to you by | MIT Libraries Authenticated Download Date | 5/9/18 11:31 AM Although PPV has spread throughout several European countries (Sochor et al, 2012), our study revealed that PPV is not widely spread in Latvia and is currently present only in a limited number of genotypes and geographical localities. One of the main reasons for the limited spread of PPV in plum orchards in Latvia could be the low prevalence of aphid species in Northern European countries (Verhoeven et al, 1998;Blystad and Munthe, 2006;Wijkamp and Gaag, 2011).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Abbreviations as in Table 2 Brought to you by | MIT Libraries Authenticated Download Date | 5/9/18 11:31 AM Although PPV has spread throughout several European countries (Sochor et al, 2012), our study revealed that PPV is not widely spread in Latvia and is currently present only in a limited number of genotypes and geographical localities. One of the main reasons for the limited spread of PPV in plum orchards in Latvia could be the low prevalence of aphid species in Northern European countries (Verhoeven et al, 1998;Blystad and Munthe, 2006;Wijkamp and Gaag, 2011).…”
Section: Discussionmentioning
confidence: 92%
“…Most PPV isolates belong to the D, M and Rec types. PPV-M is mostly known in Southern, Eastern and Central Europe, while PPV-D mostly in Western Europe (Sochor et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, various alternative management strategies had to be implemented against sharka. Even though the PPV pathosystem has been well studied (for reviews, see 47, 48, 66,82,130,135,136), the epidemiological grounds underlying sharka management strategies have never been…”
Section: Introductionmentioning
confidence: 99%
“…PPV usually affects both the leaves (leaf symptoms) and the fruit (fruit symptoms) of plants. Typical sharka symptoms on plum include chlorotic spots or rings, oak-leaf patterns and vein clearing on leaves, shallow rings and arabesque depressions on fruit, sometimes with brownish or reddish necrotic flesh (Sochor et al 2012). Fruit from infected trees may drop prematurely (Clemente-Moreno et al 2015).…”
mentioning
confidence: 99%